Intramolecular Hydroalkoxylation of Non‐Activated CC Bonds Catalysed by Zeolites: An Experimental and Theoretical Study. Issue 6 (23rd May 2013) - Pérez‐Mayoral, Elena; Matos, Ines; Nachtigall, Petr; Položij, Miroslav; Fonseca, Isabel; Vitvarová‐Procházková, Dana; Čejka, Jiří
Abstract The high activity and selectivity of zeolites in the cyclisation of unsaturated alcohols is reported for the first time; the details of a reaction mechanism based on quantum chemical calculations are also provided. The high efficiency of zeolites MFI, BEA and FAU in the cyclisation of unsaturated alcohols (cis‐decen‐1‐ol, 6‐methylhept‐5‐en‐2‐ol and 2‐allylphenol) to afford oxygen‐containing heterocyclic rings is demonstrated. The best catalytic performance is found for zeolites with the optimum concentration of Brønsted acid sites (ca. 0.2 mmol g−1) and the minimum number of Lewis acid sites. It is proposed that the efficiency of the catalysts is reduced by the existence of the so‐called dual site, at which a molecule of unsaturated alcohol can simultaneously interact with two acid sites (an OH group with one and the double bond with the other Brønsted site), which increases the interaction strength. The formation of such adsorption complexes leads to a decrease in the catalyst activity because of (i) an increase in the reaction barrier, (ii) an unfavourable conformation and (iii) diffusion limitations. A new procedure for the preparation of tetrahydrofurans and pyrans over zeolite catalysts provides important oxygen‐containing heterocycles with numerous applications.